A battery

CN122659496BActive Publication Date: 2026-10-27CALB GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611046957.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

然而,现有5V镍锰酸锂电池普遍面临循环寿命差的关键技术瓶颈,正极材料中的锰离子易在充放电循环过程中从晶格中溶出,溶出的Mn2+会随电解液迁移至负极表面并沉积,破坏SEI膜稳定性,加剧电解液与负极的副反应,最终导致电池循环性能快速衰退,难以同时平衡电池的循环寿命与安全性,严重制约了5V镍锰酸锂电池的实际应用与推广

Benefits of technology

本发明通过控制负极片的压实密度a,含有捕捉剂的功能涂层的厚度占比b,隔膜的透气度c满足特定关系式9≤a×b×c≤329,可有效吸附正极溶出的锰离子以保护SEI膜,平衡电池内部气体与热量散发,综合改善循环寿命差、安全性不足的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659496B_ABST
    Figure CN122659496B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of batteries, and in particular to a battery. The battery comprises a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises lithium nickel manganese oxide. The separator comprises a base film, at least one side of the base film is provided with a functional coating, and the functional coating comprises a capture agent. The capture agent is a material capable of coordinating with manganese ions, ion exchanging or chemically adsorbing manganese ions. The compaction density of the negative electrode sheet is denoted as a g / cm 3 ; the thickness ratio of the functional coating to the total thickness of the separator is denoted as b; the air permeability of the separator is denoted as c s / 100mL; and a, b and c satisfy the relationship: 9≤a×b×c≤329. Through dynamic matching between the three parameters a, b and c, the battery can balance the cycle life and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology

[0002] In fields such as energy storage and power batteries, 5V high-voltage lithium nickel manganese oxide (LNMO) batteries have become one of the important development directions of current electrochemical energy storage technology due to their significant advantage of high energy density. However, existing 5V lithium nickel manganese oxide batteries generally face the key technical bottleneck of poor cycle life. Manganese ions in the cathode material are easily dissolved from the crystal lattice during charge-discharge cycles, and the dissolved Mn... 2+ It will migrate to the surface of the negative electrode with the electrolyte and deposit there, destroying the stability of the SEI film, aggravating the side reactions between the electrolyte and the negative electrode, and ultimately causing the battery cycle performance to decline rapidly. It is difficult to balance the cycle life and safety of the battery at the same time, which seriously restricts the practical application and promotion of 5V nickel manganese lithium batteries. Summary of the Invention

[0003] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and provide a battery in which the compaction density a of the negative electrode sheet, the thickness ratio b of the functional coating containing the trapping agent, and the air permeability c of the separator satisfy a specific relationship 9≤a×b×c≤329, which can simultaneously improve the cycle life and safety of a 5V nickel manganese lithium battery.

[0004] To achieve the above objectives, the present invention provides a battery comprising a negative electrode and a separator, wherein the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises lithium nickel manganese oxide; the separator comprises a base membrane, the base membrane having a functional coating disposed on at least one side, the functional coating comprising a trapping agent; the trapping agent is a material capable of coordinating or exchanging ions with manganese ions, or chemically adsorbing manganese ions; The compaction density of the negative electrode sheet is denoted as ag / cm³. 3 ; The thickness percentage of the functional coating is denoted as b, based on the total thickness of the diaphragm. The air permeability of the diaphragm is denoted as cs / 100mL; a, b, and c satisfy the relation: 9 ≤ a × b × c ≤ 329.

[0005] The present invention, by adopting the above technical solution, has the following beneficial effects: This invention controls the compaction density (a) of the negative electrode, the thickness ratio (b) of the functional coating containing the trapping agent, and the air permeability (c) of the separator to satisfy a specific relationship 9≤a×b×c≤329. This effectively adsorbs manganese ions dissolved from the positive electrode to protect the SEI film, balances the dissipation of gas and heat inside the battery, and comprehensively improves the problems of poor cycle life and insufficient safety.

[0006] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to those ranges or values. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In this document, unless otherwise specified, data ranges include endpoints. Attached Figure Description

[0007] Figure 1 The diagram shown is a schematic diagram of the diaphragm structure in an example of the present invention.

[0008] Figure 2 The diagram shown illustrates the principle of manganese ion adsorption by the scavenger in the functional coating of the diaphragm in an example of the present invention. Detailed Implementation

[0009] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0010] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0011] This invention provides a battery comprising a negative electrode and a separator, wherein the positive electrode comprises a positive active material layer, the positive active material layer comprises a positive active material, and the positive active material comprises lithium nickel manganese oxide; the separator comprises a base membrane, and at least one side of the base membrane is provided with a functional coating, the functional coating comprising a trapping agent, the trapping agent being a material capable of coordinating, ion exchanging, or chemically adsorbing manganese ions; The compaction density of the negative electrode sheet is denoted as ag / cm³. 3 ; The thickness percentage of the functional coating is denoted as b, based on the total thickness of the diaphragm. The air permeability of the diaphragm is denoted as cs / 100mL; a, b, and c satisfy the relation: 9 ≤ a × b × c ≤ 329.

[0012] This invention utilizes a functional coating containing a scavenging agent within the separator to absorb manganese ions dissolved from the positive electrode, preventing them from precipitating and damaging the SEI film at the negative electrode, thus improving battery cycle life. While a larger percentage (b) of the functional coating containing the scavenging agent (i.e., containing more scavenging agent) can effectively improve cycle life, excessive scavenging agent can clog the separator, hindering the dissipation of gas and heat within the cell, leading to reduced battery safety. Therefore, further reducing the separator's permeability (c) is necessary to improve its air permeability, thereby facilitating the dissipation of gas and heat within the cell and improving battery safety. Similarly, a higher negative electrode compaction density (a) can improve battery energy density, but excessively dense negative electrode particles can compress lithium-ion diffusion channels, exacerbating the risk of lithium dendrite growth. Therefore, reducing the separator's permeability (c) (to further improve air permeability) or reducing the percentage (b) of the functional coating's thickness (sacrificing some of the scavenging capacity of the functional coating to release porosity) is necessary to ensure cycle life while avoiding safety degradation. When the negative electrode compaction density 'a' is low, the larger gaps between negative electrode particles facilitate smooth lithium-ion transport and reduce the likelihood of lithium dendrite formation. However, this intensifies side reactions between the electrolyte and the negative electrode, leading to faster SEI film consumption and decreased cycle life. In this case, a larger 'b' (increasing the thickness of the functional coating to enhance manganese ion absorption) or a larger 'c' (increasing membrane permeability to hinder manganese ion diffusion) is needed to compensate for the loss in cycle life. Simultaneously, the lower risk of lithium dendrite formation due to a smaller 'a' balances battery safety. In summary, this invention, through dynamic matching of the three parameters 'a', 'b', and 'c', enables the battery to balance cycle life and safety.

[0013] Furthermore, when a×b×c exceeds the upper limit (>329), the excessively high negative electrode compaction density a will compress the diffusion channels of lithium ions between the graphite layers of the negative electrode. During charging, lithium ions cannot be embedded into the negative electrode lattice in time and are reduced on the surface to form metallic lithium dendrites. Additionally, the thickness ratio b of the functional coating in the separator is too large, although it increases Mn... 2+ While increasing chelation, it also exacerbates pore blockage. The combined effect significantly increases the probability of lithium dendrites piercing the separator and causing internal short circuits. Furthermore, excessively high separator permeability (c) leads to higher separator density, hindering heat and gas dissipation. This heat accumulation intensifies side reactions, resulting in deterioration of battery safety and cycle performance. When a×b×c is below the lower limit (<9), the low negative electrode compaction density (a) increases the gaps between active material particles, accelerates the electrolyte wetting rate, and exacerbates interfacial side reactions between the negative electrode and electrolyte (such as solvent decomposition). Simultaneously, the small proportion of the functional coating thickness (b) in the separator reduces the scavenging effect on Mn. 2+ Decreased chelation efficiency and excessively low permeability (c) result in membranes with high permeability allowing manganese ions to easily pass through without effective interception, leading to a large amount of unchelated Mn. 2+Migration to the negative electrode disrupts the stability of the SEI film, and the dual effect significantly shortens the battery cycle life. In summary, this invention precisely balances "Mn" through the quantitative synergistic relationship of a, b, and c. 2+ The contradiction between chelation efficiency, lithium-ion transport efficiency, and heat and gas conduction efficiency effectively solves the technical bottleneck of the existing 5V nickel-manganese lithium battery, which has poor cycle life and insufficient safety.

[0014] For example, the value of a×b×c can be 9, 12, 15, 18, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 329 or any value between the two points mentioned above.

[0015] In some implementations, a, b, and c satisfy the relationship: 29 ≤ a × b × c ≤ 149. For example, they can be 29, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 145, 149, or any value between the two points mentioned above. Further controlling the value of a × b × c within the above range achieves a better match between basic cycle life and safety. This avoids the problems of insufficient manganese ion capture and inadequate SEI film protection caused by an excessively thin functional coating or an overly permeable membrane when the value of a × b × c is close to the lower limit. It also avoids safety risks such as heat and gas accumulation and accelerated lithium dendrite growth that may occur when the value of a × b × c is close to the upper limit due to an excessively thick functional coating or an overly dense membrane.

[0016] In some implementations, 'a' satisfies: 1.2 ≤ a ≤ 1.8, meaning the compaction density of the negative electrode sheet can be, for example, 1.2 g / cm³. 3 1.3 g / cm 3 1.4 g / cm 3 1.5 g / cm 3 1.6 g / cm 3 1.7 g / cm 3 1.8 g / cm 3 Alternatively, any value between the two points mentioned above, preferably 1.4 ≤ a ≤ 1.6. The compaction density of the negative electrode sheet should satisfy the above range to balance the diffusion efficiency of lithium ions in the negative electrode and the structural stability of the active material. If the compaction density of the negative electrode sheet is too high (>1.8), it compresses the diffusion path of lithium ions between the graphite layers. During charging, lithium ions cannot be inserted in time, which can easily form lithium dendrites that pierce the separator and cause internal short circuits. If the compaction density of the negative electrode sheet is too low (<1.2), the gaps between the particles of the negative electrode active material are large, the electrolyte wets too quickly, aggravates the side reactions between the negative electrode and the electrolyte, damages the stability of the SEI film, and shortens the cycle life.

[0017] In some embodiments, b satisfies: 0.063 ≤ b ≤ 0.375, meaning the ratio of the functional coating thickness to the diaphragm thickness can be 6.3%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, 35%, 37.5%, or any value between the above two points, preferably 0.11 ≤ b ≤ 0.29. A functional coating thickness ratio within the above range ensures Mn 2+ The chelation efficiency must be optimized while avoiding clogging of the membrane pores. If the functional coating thickness is too large (>37.5%), excessive scavenger will clog the membrane pores, preventing the internal gas and heat from escaping and increasing the risk of thermal runaway and short circuits. If the functional coating thickness is too small (<6.3%), insufficient scavenger will make it difficult to chelate the Mn dissolved from the cathode. 2+ Free Mn 2+ Migrating to the negative electrode damages the SEI film, resulting in a significant decrease in cycle life.

[0018] In some embodiments, c satisfies: 100 ≤ c ≤ 600, meaning the permeability of the separator can be, for example, 100, 160, 200, 300, 400, 460, 500, 600, or any value between the two above, preferably 160 ≤ c ≤ 400. Membrane permeability within this range ensures timely dissipation of heat / gas inside the cell while maintaining normal lithium-ion conduction. If the separator permeability is too high (>600), poor permeability leads to heat and gas accumulation that cannot be released, causing a sudden rise in battery temperature and reduced safety. If the separator permeability is too low (<100), the separator pores are too large, reducing mechanical strength and making it prone to micro-short circuits between the positive and negative electrodes. Furthermore, excessive electrolyte wetting exacerbates side reactions, impairing cycle stability.

[0019] In some embodiments, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite, and the particle size Dv50 of the negative electrode active material layer is 16µm-26µm, for example, it can be 16µm, 18µm, 20µm, 22µm, 24µm, 26µm or any value between the above two points.

[0020] Meeting the above-mentioned range for the particle size Dv50 of the negative electrode active material layer ensures a suitable lithium-ion diffusion path, balancing conductivity and electrolyte wetting. Simultaneously, meeting the above-mentioned compaction density range for the negative electrode sheet improves the density of the active material and enhances electrode conductivity. If the particle size Dv50 of the negative electrode active material layer is greater than 26µm, the lithium-ion diffusion path is prolonged, and fast-charging performance decreases. If the particle size Dv50 of the negative electrode active material layer is less than 16µm, the specific surface area increases, leading to increased side reactions with the electrolyte and making the SEI film more susceptible to damage.

[0021] In some embodiments, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and the particle size Dv50 of the negative electrode active material layer is in the range of 16µm-26µm, for example, it can be 16µm, 18µm, 20µm, 22µm, 24µm, 26µm or any value between the above two points.

[0022] Silicon-based materials exhibit high lithium intercalation expansion rates. The particle size of silicon-based materials allows for expansion buffer space, resulting in a relatively lower compaction density for the corresponding anode sheet compared to carbon-based anode materials. This alleviates expansion stress and prevents electrode structure damage. However, if the particle size (Dv50) of the anode active material layer is greater than 30µm, expansion stress concentrates, and the particles are prone to pulverization. Conversely, if the particle size (Dv50) is less than 16µm, the specific surface area is too large, leading to repeated rupture of the SEI film and a sharp drop in cycle life.

[0023] In some embodiments, the silicon content, based on the total mass of the negative electrode active material layer, is 5%-20%, for example, it can be 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, or any value between the above two points. A silicon content within this range balances the high capacity advantage of silicon-based materials with the volume expansion problem, while ensuring electrode electron conduction efficiency and avoiding safety risks. If the silicon content is too high (>20%), the silicon lithium intercalation expansion rate increases dramatically, exacerbating electrode structure cracking and significantly reducing cycle life; if the silicon content is too low (<5%), the silicon particles are sparse, becoming electron transport barriers, resulting in uneven local current density, increased risk of lithium metal deposition, and reduced battery safety.

[0024] The testing method for silicon includes the following steps: 1) Pretreatment: Discharge the battery to the lower limit voltage of 3.5V at 0.33C. Take the electrode sheet of the lithium-ion battery in the empty state and soak it in dimethyl carbonate (DMC) solution at room temperature for 4 hours. After soaking, take out the electrode sheet and dry it in a vacuum environment. Use a ceramic knife to scrape off the active material powder on the surface of the electrode sheet. 2) The silicon content in the negative electrode sheet was tested using the alkali-soluble-ICP method. The negative electrode active material layer powder was scraped off. A sample of the powder was weighed and placed in a nickel crucible pre-filled with potassium hydroxide. A small amount of potassium hydroxide was added to cover the sample surface, and two drops of ethanol were added. The mixture was heated on an electric furnace until the potassium hydroxide melted and dehydrated. Then, it was transferred to a muffle furnace at 1100℃ and kept at this molten temperature for 8 hours. The nickel crucible was removed and allowed to cool slightly. The sample was placed in a 300 mL plastic beaker, and hot water was added for extraction. After the reaction, the crucible was washed out. HCl was added to the extract for acidification, and hydrogen peroxide and hydrochloric acid were added to form a mixed acid to ensure a more complete conversion of silicon compounds to silicon ions. After cooling, the extract was washed out with water and transferred to a 100 mL volumetric flask. The volume was adjusted, and the solution was shaken well. After standing, the solution was transferred to another 100 mL volumetric flask, adjusted to volume, shaken well, and allowed to stand until clear to obtain the test solution. Simultaneously, a blank solution was prepared as a control. No powder was added to the blank solution. Following the operating procedure, a blank sample control was prepared to eliminate any potential influences from the operation. ICP testing was performed on the test solution. The elemental detection wavelength was selected, and the experimental conditions were set: based on the sample characteristics and the ICP testing of the test solution, the Si elemental detection wavelength of 288.158 nm was selected. The Si content of the element was determined by ICP testing.

[0025] This invention also provides a method for preparing a negative electrode, comprising the following steps: A negative electrode active material, conductive agent, binder, and dispersant are mixed and a solvent is added to obtain a negative electrode slurry, wherein the mass percentage of negative electrode active material: conductive agent: binder: dispersant is (90-98):(0-5):(1.5-5):(0.3-1.5). The negative electrode slurry is coated on at least one surface of the negative electrode current collector, and after drying, rolling, and slitting, a negative electrode sheet is obtained.

[0026] In some embodiments, the negative electrode active material is selected from carbon materials, silicon-based materials, and lithium titanate (Li4Ti5O). 12 One or more of the following.

[0027] Specifically, the carbon material can be selected from one or more of the following: natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, and soft carbon.

[0028] Specifically, the silicon-based material can be selected from one or more of elemental silicon, silicon oxides, silicon carbide compounds, and silicon alloys.

[0029] Specifically, the conductive agent is selected from one or more of superconducting carbon (SP), conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0030] Specifically, the adhesive is selected from at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and sodium carboxymethyl methyl ester (CMC).

[0031] Specifically, the dispersant is selected from at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), and polyvinylpyrrolidone (PVP).

[0032] Specifically, the negative electrode current collector is selected from metal foil or composite current collector; the metal foil can be copper or copper alloy; the composite current collector includes a middle high layer and metal layers disposed on both sides of the polymer layer, wherein the polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers; the metal layer is selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.

[0033] Specifically, the solvent is water.

[0034] In some embodiments, the capturing agent is a material capable of coordinating with manganese ions, ion exchanging, or chemically adsorbing manganese ions. Those skilled in the art can select materials with the aforementioned functions as needed. Exemplarily, the capturing agent includes at least one of the following: ethylenediaminetetraacetic acid (EDTA), aza-15-crown ether-5 polymer, ammonium dihydrogen phosphate, lithium aluminum titanium phosphate (LATP), lanthanum lithium titanate (LLTO), and barium titanate.

[0035] In some embodiments, a ceramic coating is disposed on at least one surface of the base film, and the functional coating is disposed on the surface of the ceramic coating away from the base film, with the ceramic coating located between the base film and the functional coating.

[0036] In some implementations, such as Figure 1As shown, a functional coating is disposed on one side of the base membrane, and a ceramic coating is disposed on the other side. A schematic diagram illustrating the principle of manganese ion adsorption by the scavenger in the functional coating of the diaphragm is shown below. Figure 2 .

[0037] In some embodiments, the total thickness of the separator is 10µm-25µm, for example, it can be 10µm, 12µm, 14µm, 16µm, 18µm, 20µm, 22µm, 25µm or any value between the above two points. If the total thickness of the separator is too large, the air permeability of the separator will be too small, making it difficult for heat inside the cell to be transferred to the outside, resulting in poor battery safety; if the total thickness of the separator is too small, the side reactions between the electrolyte and the positive and negative electrodes will increase, and the cycle life will decrease.

[0038] In some embodiments, the thickness of the base film is 9µm to 12µm; In some embodiments, the thickness of the functional coating is 1µm to 6µm; In some embodiments, the thickness of the ceramic coating is 1µm to 3µm.

[0039] In some embodiments, the porosity of the base membrane is 30% to 60%, for example, it can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, or any value between the above two points.

[0040] The method for testing the porosity of the base membrane includes the following steps: Sample preparation and drying: Cut a base film with an area of ​​4cm×12cm, vacuum dry it at 40-50℃ for 2 hours to remove moisture and residual solvent, and weigh it as md (dry weight). Immersion and absorption: Immerse the sample completely in n-butanol for 1-2 hours to ensure that the pores are fully saturated; Dry and weigh: Quickly remove the sample and gently blot the surface of any residual liquid with filter paper (be careful not to squeeze the liquid out of the hole), and weigh it immediately and record it as mw (wet weight). Volume measurement: Use a micrometer or thickness gauge to measure the average thickness of the sample and calculate the apparent volume V (length × width × thickness).

[0041] Calculation formula: ε: Porosity (%) ρ l The density of the wetting solution (n-butanol approximately 0.81 g / cm³) 3 Hexadecane approximately 0.77 g / cm³ 3 ) V: Apparent volume of the basement membrane (cm³) 3 ).

[0042] The present invention also provides a method for preparing a diaphragm, which specifically includes the following steps: Materials such as a scavenging agent, binder, and conductive agent (optionally) are dispersed in a solvent to form a uniform slurry, which is then coated onto a base membrane (such as PE, PP, or ceramic separator). The active material is a manganese ion scavenging agent, which needs to be ground into submicron or nanoscale powder to increase specific surface area and dispersibility.

[0043] In some specific embodiments, the adhesive is selected from any one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), with PVDF being preferred. The adhesive provides adhesion between the coating and the base film.

[0044] In some specific implementations, the mass ratio of the trapping agent to the binder is (95-98):(2-5).

[0045] In some specific implementations, the solvent is used to dissolve the binder, such as N-methylpyrrolidone (NMP) (for dissolving PVDF), or deionized water (for dissolving water-based binders such as SBR and CMC).

[0046] In some specific implementations, conductive agents are used to improve the ion / electron distribution on the membrane surface, but this is not necessary; for example, carbon black (Super P) or carbon nanotubes (CNTs) can be selected.

[0047] In some specific embodiments, the preparation of the slurry of the diaphragm includes the following steps: slowly adding a binder (such as PVDF) to a solvent (such as NMP), stirring magnetically until completely dissolved to form a clear and transparent adhesive; gradually adding a trapping agent powder (and a conductive agent) to the adhesive; and using a planetary centrifugal mixer for high-speed shearing and stirring to ensure that the particles are fully dispersed and avoid agglomeration, thereby obtaining a slurry with uniform viscosity and stable suspension.

[0048] In some embodiments, the coating methods include blade coating, dip-coating, and spray coating. Specifically, blade coating involves fixing the diaphragm onto a flat substrate and using an adjustable-height blade to apply the slurry to the surface. The coating thickness is controlled by the gap between the blade and the base film. Dip-coating involves immersing the base film in the slurry and vertically pulling it out at a constant and slow speed, resulting in a uniform liquid film adhering to the surface. The thickness is controlled by the slurry viscosity and the pulling speed. Spray coating involves atomizing the slurry with a spray gun and spraying it onto the diaphragm surface. This method is suitable for preparing thinner coatings where high uniformity control is required.

[0049] In some embodiments, the method for preparing the diaphragm further includes a drying and post-treatment step after the coating step.

[0050] Specifically, the drying and post-processing steps include drying, rolling, and cutting. Drying includes placing the coated wet separator in a vacuum drying oven and drying it at a suitable temperature (e.g., 60-80°C) for a sufficient time (e.g., 12 hours) to completely remove the solvent (NMP or water). Rolling includes: after drying, light hot pressing (cold pressing is also acceptable) can be performed using a roller mill to make the coating structure denser and smoother, and to enhance its adhesion to the base film. Cutting includes: finally cutting the large separator sheet into the dimensions required for the battery cell.

[0051] In some embodiments, the battery includes a positive electrode sheet, wherein the mass ratio of nickel to manganese in the positive electrode active material layer is 0.25-0.43, for example, it can be 0.25, 0.3, 0.35, 0.4, 0.43, or any value between these two points. If the nickel-manganese mass ratio is too high, it will accelerate the oxidation and decomposition of the electrolyte, releasing heat and reducing battery safety. If the nickel-manganese mass ratio is too low, manganese ions are easily dissolved from the crystal lattice and deposited on the surface of the negative electrode, damaging the SEI film and reducing cycle life.

[0052] In some embodiments, the particle size Dv50 of the positive electrode active material layer is 6µm-12µm, for example, it can be 6µm, 7µm, 8µm, 9µm, 10µm, 11µm, 12µm or any value between the above two points. If the particle size Dv50 of the positive electrode active material layer is too large, the lithium-ion transport path is lengthened and the fast charging performance decreases; if the particle size Dv50 of the positive electrode active material layer is too small, the side reactions with the electrolyte increase, the dissolution of manganese increases, and the cycle life decreases.

[0053] In some embodiments, the lithium nickel manganese oxide includes a doping element, which includes one or more of zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), tin (Sn), yttrium (Y), aluminum (Al), zinc (Zn), fluorine (F), phosphorus (P), and sulfur (S).

[0054] In some embodiments, the lithium nickel manganese oxide surface is provided with a coating layer, the coating layer comprising a coating material selected from one or more oxides of zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), tin (Sn), yttrium (Y), aluminum (Al), zinc (Zn), fluorine (F), phosphorus (P), and sulfur (S).

[0055] This invention improves the structural stability of lithium nickel manganese oxide and reduces manganese leaching by doping and / or coating the aforementioned elements, thereby enhancing cycle life.

[0056] In some embodiments, the porosity of the positive electrode is 20%-40%, for example, it can be 20%, 25%, 30%, 35%, 40%, or any value between the above two points. If the porosity of the positive electrode is too large, the side reactions between the positive electrode and the electrolyte will increase, manganese dissolution will increase, and the cycle life will decrease; if the porosity of the positive electrode is too small, lithium-ion transport will be hindered, and fast charging performance will decrease.

[0057] Methods for testing the porosity of positive electrode sheets include: 1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage of 3.5V, remove the empty battery, disassemble the electrodes, and soak the electrodes in dimethyl carbonate (DMC) solution for 4 hours; then air dry. 2) Subsequently, the electrode is cut into 12mm diameter discs using an electrode punching machine. Simultaneously, the thickness of the electrode and the current collector is measured using a thickness gauge, denoted as h1 and h2 respectively. The mass is recorded as m1 using a balance with an accuracy of 0.001g. The volume v of the cut electrode is calculated using the formula v = πr²(h1 - h2). The electrode is then immersed in a sealed container with a certain volume of hexadecane for 1 hour (the volume of hexadecane in the sealed solution is not critical, but the required amount must ensure complete immersion of the electrode). After 1 hour, the electrode is removed with tweezers and placed on filter paper to absorb dry until constant weight (generally, 1 hour is sufficient). The mass is then recorded as m2. The porosity is calculated using the formula X / v, where X = (m2 - m1) / ρ, and ρ is the density of hexadecane, 0.7734 g / cm³. 3 .

[0058] In some embodiments, the sheet resistance of the positive electrode is 100mΩ-300mΩ, for example, it can be 100mΩ, 150mΩ, 200mΩ, 250mΩ, 300mΩ, or any value between these two points. If the sheet resistance of the positive electrode is too high, poor contact between the active material particles will significantly increase ohmic polarization heat, increase heat generation, and reduce battery safety. If the sheet resistance of the positive electrode is too low, the contact area between the electrolyte and the active material will be large, accelerating interfacial side reactions and reducing cycle life.

[0059] The methods for testing the surface resistivity of the positive electrode include: Sample preparation: Take the rolled electrode sheet and cut it into a rectangle of 50 mm × 60 mm. Under normal temperature and humidity conditions of ≤60%, use an electrode sheet surface resistance tester to test the surface resistance of the electrode sheet at 5 points and take the average value.

[0060] This invention also provides a method for preparing a positive electrode, comprising the following steps: The positive electrode active material is mixed with a conductive agent and a binder, and a solvent is added to obtain a positive electrode slurry, wherein the mass percentage of positive electrode active material: conductive agent: binder is (90%-99%): (0.5%-5%): (0.5%-5%). The positive electrode slurry is coated on at least one surface of the positive electrode current collector, and after drying, rolling, and slitting, a positive electrode sheet is obtained.

[0061] The positive electrode active material is lithium nickel manganese oxide (LNMO), a spinel-structured positive electrode active material with high voltage characteristics. 1+x Ni y N z Mn 2-x-y-z O 4-k -0.1≤x≤0.2,0.4≤y≤0.6,0≤z≤0.2,0≤k≤0.1, where N is a doping element, including but not limited to one or more of Cr, Mo, Nb, Ru, P, Si, S, Ta, W and Ti.

[0062] For example, the conductive agent is selected from at least one of superconducting carbon (SP), acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0063] For example, the adhesive is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0064] For example, the positive current collector can be a metal foil or a composite current collector; specifically, the metal foil can be aluminum or an aluminum alloy; the composite current collector includes a middle high layer and metal layers disposed on both sides of the polymer layer, wherein the polymer layer includes a polymer material, which includes at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers. The metal layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.

[0065] For example, the solvent is selected from NMP.

[0066] In some embodiments, the battery includes an electrolyte, which includes additives, including any one or a combination of vinylene carbonate (VC) and fluoroethylene carbonate (FEC). The additives constitute 0.1%-5% of the total mass of the electrolyte, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, or any value between these two points. Adding these additives to the electrolyte can, on the one hand, improve lithium-ion transport efficiency, reduce electrochemical polarization and concentration polarization heat, and enhance safety; on the other hand, it promotes the formation of the SEI film on the negative electrode, reduces side reactions between the negative electrode and the electrolyte, and improves cycle life.

[0067] In some embodiments, the electrolyte includes a carboxylic acid ester solvent, which is selected from at least one of methyl formate (MF), ethyl acetate (EA), methyl acetate (MA), and methyl propionate (MP). The solvent accounts for 5%-50% of the total mass of the electrolyte, for example, 5%, 10%, 20%, 30%, 40%, 50%, or any value between these two points. Adding the above solvent to the electrolyte can, on the one hand, reduce the viscosity of the electrolyte, reduce lithium-ion migration resistance, reduce concentration polarization and electrochemical polarization heat, and improve safety; on the other hand, it promotes the formation of the SEI film on the negative electrode, reduces the damage to the SEI film caused by manganese leaching, and improves cycle life.

[0068] In some embodiments, the electrolyte further includes a carbonate solvent selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, and fluoroethylene carbonate.

[0069] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP), and the lithium salt concentration in the electrolyte is 0.5 mol / L to 2.5 mol / L.

[0070] The test method for the content of additives, solvents and lithium salts in electrolytes includes the following steps: 1) Electrolyte Collection: If the electrolyte of the test object is in the battery, use a battery charging and discharging device to discharge the battery under the following conditions: current 0.3C, cutoff voltage. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte. There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing tape to prevent electrolyte leakage. ② if there is no free electrolyte, use a hydraulic press to continuously pressurize until free electrolyte appears, collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix thoroughly with the dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue. 2) Inject the collected electrolyte sample into a gas chromatography-mass spectrometry (GC-MS) instrument using a microsyringe to obtain GC-MS chromatograms. Dissolve the electrolyte additive in EMC solvent to prepare solutions of different concentrations, and inject them into the GC-MS instrument to obtain standard GC-MS chromatograms. Compare the GC-MS chromatogram of the electrolyte to be tested with the standard GC-MS chromatogram to confirm whether the corresponding components are present. Then, determine the content of each component based on the peak area of ​​each component in the electrolyte to be tested. If the electrolyte to be tested is a finished product, the component content can be determined directly by comparing it with the standard GC-MS chromatogram, without the need for electrolyte collection.

[0071] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0072] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.

[0073] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.

[0074] Example 1 1) Preparation of positive electrode sheet: LNMO:SP:PVDF:CNT (mass ratio 95:1.5:2.5:1) was dispersed in NMP to obtain a positive electrode slurry; this slurry was coated onto aluminum foil to obtain a double-sided coated positive electrode sheet; subsequently, it was rolled and cut to obtain the positive electrode sheet; the areal density of the positive electrode sheet was 350 g / m³. 2 The compacted density is 3.0 g / cm³. 3 ; 2) Negative electrode preparation: Graphite, conductive agent SP, binder SBR, and dispersant CMC were mixed evenly in a mass ratio of 96:0.6:1.4:2 and dispersed in deionized water to obtain a negative electrode slurry. This negative electrode slurry was then coated onto copper foil to obtain a double-sided coated electrode sheet. After rolling and cutting, the negative electrode sheet was obtained with an areal density of 130 g / m³. 2 The compacted density is 1.6 g / cm³. 3 .

[0075] 3) Preparation of electrolyte: Ethylene carbonate (VC), ethyl acetate (EA), and methyl acetate (MA) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0076] 4) Preparation of the diaphragm: The capture agent LATP was ground into powder with a particle size of 0.5~1µm to increase the specific surface area and dispersibility.

[0077] The binder (PVDF) is slowly added to the solvent (N-methylpyrrolidone) and magnetically stirred until completely dissolved, forming a clear and transparent adhesive solution. The trapping agent powder is then gradually added to the adhesive solution, and a planetary centrifugal mixer is used for high-speed shear stirring to ensure full particle dispersion and prevent agglomeration, resulting in a slurry with uniform viscosity and stable suspension, which is then used to prepare a uniform functional coating. The mass ratio of the trapping agent to the binder is 95-98:2-5. Select a PE base film with a thickness of 10µm, and coat its surface with an alumina ceramic coating with a thickness of 2µm. Apply the functional coating slurry to the surface of the ceramic coating with a coating thickness of 1.5µm (coating method ①).

[0078] The coated wet separator is placed in a vacuum drying oven and dried at 70°C for a sufficient time (12 hours) to completely remove the solvent. After drying, it can be lightly hot-pressed using a roller mill to make the coating structure denser and smoother, and to enhance its adhesion to the base film. Finally, the large sheet of separator is cut into the size required for the battery cell.

[0079] 5) Assembly and formation: The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. Then, they are wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.

[0080] Battery test ① Test method for compaction density of negative electrode sheet: 1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage of 3.5V, take out the empty battery, disassemble the electrode, soak the electrode in dimethyl carbonate (DMC) solution for 4 hours, and then air dry; 2) Use a punching machine to punch the pretreated negative electrode sheet into circular sheets of a fixed area, denoted as S0. Take three circular sheets as parallel samples, and weigh each of the three circular sheets using an electronic balance. Take the average value and record it as M1. Use a micrometer to measure the thickness of the active material layer in each of the three circular sheets (i.e., the total thickness minus the current collector), and take the average value and record it as H. Finally, add an appropriate amount of deionized water to each of the three circular sheets, gently wipe off the coating on the sheets with lint-free paper to expose the copper foil, and let them stand at room temperature (or dry) for 10 minutes. After the copper foil is dry, weigh each of the three copper foil sheets, take the average value and record it as M0. Calculate the compaction density of the negative electrode sheet using the following formula: a = (M1 - M0) / (H × S0) ② Test method for the proportion of functional coating thickness in diaphragm thickness: Pretreatment: The battery is discharged at 0.33C to the lower limit voltage of 3.5V. The lithium-ion battery in the empty state is disassembled to obtain the separator; Liquid nitrogen brittle fracture method: The diaphragm sample is immersed in liquid nitrogen until it becomes brittle, and then quickly broken to obtain a clear cross-section, avoiding coating deformation. The diaphragm sample is fixed to the sample stage with conductive adhesive, with the cross-section facing upwards. For non-conductive diaphragms, gold or carbon sputtering is required to prevent charge accumulation.

[0081] Obtain a cross-sectional SEM image of the diaphragm. Locate a clear cross-sectional image in the SEM software and use the built-in ruler function to directly measure the thickness of the functional coating and the total diaphragm thickness at 10 points on the image (measure the particle size of the trapping agent; the particle size indicates the functional coating containing the trapping agent). The thickness of the ceramic coating can also be measured using this method. The percentage of functional coating thickness = (functional coating thickness / total diaphragm thickness) × 100%.

[0082] ③ Test method for diaphragm air permeability: The battery was discharged to 3.5V at 0.33C, the empty battery was removed, the separator was disassembled and soaked in DMC solvent for 10 minutes to obtain the separator sample. Using a separator permeability tester, in an environment with relative humidity <2%RH and 101.3KPa±5KPa, the tester applied a pressure of 1.21KPa to test the time it took for 100mL of air to pass through the separator sample with an area of ​​6.45cm2.

[0083] ④ Test method for particle size of negative electrode active material: Sample pretreatment: The battery was discharged at 0.33C to the lower limit voltage of 3.5V. The lithium-ion battery in the empty state was disassembled to obtain the electrode sheet. The negative electrode sheet was immersed in DMC (dimethyl carbonate) at room temperature for 60 minutes, taken out, and dried at room temperature with humidity ≤15%. Based on the negative electrode, the negative electrode active material layer on the surface of the current collector was scraped off.

[0084] Using a laser particle size distribution measuring instrument (Mastersizer3000), the particle size distribution is measured according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage reaching 50% is Dv50.

[0085] ⑤ Test method for the nickel / manganese ratio in the positive electrode active material layer: 1) Pretreatment: Discharge the battery to the lower limit voltage of 3.5V at 0.33C, disassemble the empty lithium-ion battery, disassemble the lithium-ion battery to obtain the electrode sheets, immerse the positive or negative electrode sheets in DMC (dimethyl carbonate) at room temperature for 60 minutes, take them out and dry them at room temperature with humidity ≤15%; based on the positive electrode, scrape off the positive electrode active material layer on the surface of the current collector; 2) Accurately weigh 0.5g of positive electrode material powder, disperse it in 20ml of water, add 10ml of nitric acid, mix thoroughly, and heat to dissolve the positive electrode material powder. Then, dilute the mixture to 100mL with water to obtain the test solution. Perform ICP testing on the test solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. Dilute the 1000mg / L standard solution with deionized water to different concentrations (generally 0, 1mg / 100mL, 2mg / 100mL, 3mg / 100mL), and select the element detection wavelength. Set the experimental conditions: Based on the characteristics of the sample and the element to be detected, set appropriate ICP instrument operating conditions: gas flow rate 0.5L / min, power 1150W, and select the element detection wavelength (Ni wavelength 231.604nm, Mn wavelength 257.61nm). The ICP testing software's self-analysis function can read the element content in the sample. ⑥ Test method for Dv50 of positive electrode active material layer: Sample pretreatment: The battery was discharged at 0.33C to the lower limit voltage of 3.5V. The lithium-ion battery in the empty state was disassembled to obtain the electrode sheet. The positive electrode sheet was immersed in DMC (dimethyl carbonate) at room temperature for 60 minutes, taken out, and dried at room temperature with humidity ≤15%. Based on the positive electrode, the positive active material layer on the surface of the current collector was scraped off.

[0086] The particle size distribution of the positive electrode active material is measured using a laser particle size distribution measuring instrument (Mastersizer3000) according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage reaching 50% is Dv50.

[0087] ⑦ Battery safety testing methods: Adiabatic Rate Calorimeter (ARC) was used to conduct thermal runaway tests on batteries under adiabatic conditions. The process involved first heating the battery, then pausing heating after every 0.5°C increase to monitor for self-heating. Once self-heating was detected, the adiabatic tracking phase began, recording the temperature-time curve. When the battery's temperature rise rate in the adiabatic environment was ≥0.02°C / min, the system determined that T1 had been reached; when the rate was ≥1°C / min, it was defined as T2. The maximum temperature (T3) on the thermal runaway curve was recorded. T2 was defined as the thermal runaway trigger temperature.

[0088] ⑧ Test method for cycle life: The lithium-ion batteries prepared in the examples and comparative examples were subjected to cycle tests at 25°C according to the following procedure: 1) Charge at a constant current rate of 1C to 4.8V, and then charge at a constant voltage until the current drops to 0.05C; 2) Let stand for 10 minutes; 3) Discharge to 3.5V at a 1C rate; 4) Let stand for 10 minutes. Perform cycle tests according to steps 1)-4) until the capacity of the lithium-ion battery is less than 80% of the initial capacity, and record the number of cycles.

[0089] The test was conducted according to Example 1. The main differences between the other examples and comparative examples are shown in Tables 1-3 below. The test performance data is shown in Table 4, as detailed below: In the examples and comparative examples, the compaction density α of the negative electrode sheet and the particle size D50 of the negative electrode active material layer were controlled by comprehensively changing the average particle size D50 of the raw material, the crushing pressure, and the rolling pressure of the negative electrode sheet. The average particle size of the raw material graphite for the negative electrode active material is 45~50µm. It is crushed by airflow at a crushing pressure of 0.4-1MPa, and the rolling pressure of the negative electrode sheet is 2T~8T. For specific parameter changes, please refer to Table 2.

[0090] In the examples and comparative examples, the thickness of the functional coating and its proportion b were adjusted by selecting base films of different thicknesses and base films with ceramic coatings of different thicknesses, and by changing the gap of the diaphragm doctor blade. The air permeability c of the diaphragm was comprehensively controlled by changing the porosity of the base film and the proportion b of the functional coating thickness, as shown in Tables 1 and 3. In Table 3, the coating methods for the functional coating are: ① the base film is a PE film, with a ceramic coating on one side of the PE film, and the functional coating is applied to the surface of the ceramic coating; ② the base film is a PE film, with a ceramic coating on one side of the PE film and a smooth functional coating on the other side.

[0091] Table 1 Table 2 Table 3 Table 4 As can be seen from Tables 1-4, by controlling the compaction density (a) of the negative electrode sheet, the thickness ratio (b) of the functional coating containing the trapping agent, and the air permeability (c) of the separator to satisfy the specific relationship 9≤a×b×c≤329, the present invention can simultaneously improve the cycle life and safety performance of the battery.

[0092] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications or equivalent substitutions made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A battery, characterized in that, The battery includes a positive electrode, a negative electrode, and a separator; the positive electrode includes a positive active material layer, the positive active material layer includes a positive active material, and the positive active material includes lithium nickel manganese oxide; The diaphragm includes a base membrane, and a functional coating is provided on at least one side of the base membrane. The functional coating contains a trapping agent, which is a material capable of coordinating with manganese ions, ion exchanging or chemically adsorbing manganese ions. The compaction density of the negative electrode sheet is denoted as ag / cm³. 3 ; The thickness percentage of the functional coating is denoted as b, based on the total thickness of the diaphragm. The air permeability of the diaphragm is denoted as cs / 100mL; a, b, and c satisfy the relation: 9 ≤ a × b × c ≤ 329.

2. The battery according to claim 1, characterized in that, a, b, and c satisfy the relation: 29 ≤ a × b × c ≤ 149.

3. The battery according to claim 1, characterized in that, a satisfies: 1.2 ≤ a ≤ 1.8; And / or, b satisfies: 0.063 ≤ b ≤ 0.375; And / or, c satisfies: 100≤c≤600.

4. The battery according to claim 1, characterized in that, a satisfies: 1.4 ≤ a ≤ 1.6; And / or, b satisfies: 0.11 ≤ b ≤ 0.29; And / or, c satisfies: 160≤c≤400.

5. The battery according to claim 1, characterized in that, The negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite, and the particle size Dv50 of the negative electrode active material layer is 16µm-26µm.

6. The battery according to claim 1, characterized in that, The negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and the particle size Dv50 of the negative electrode active material layer is in the range of 16µm-26µm.

7. The battery according to claim 5, characterized in that, The silicon content is 5%-20% based on the total mass of the negative electrode active material layer.

8. The battery according to claim 1, characterized in that, The capturing agent includes at least one of ethylenediaminetetraacetic acid, aza-15-crown-5 polymer, ammonium dihydrogen phosphate, lithium aluminum titanium phosphate, lanthanum lithium titanate, and barium titanate.

9. The battery according to claim 1, characterized in that, The base film has a ceramic coating on at least one side surface, and the functional coating is disposed on the surface of the ceramic coating away from the base film, with the ceramic coating located between the base film and the functional coating.

10. The battery according to claim 1, characterized in that, The base film has a functional coating on one side and a ceramic coating on the other side.

11. The battery according to claim 9 or 10, characterized in that, The thickness of the base film is 9µm~12µm; And / or, the thickness of the functional coating is 1µm to 6µm; And / or, the thickness of the ceramic coating is 1µm to 3µm.

12. The battery according to claim 1, characterized in that, The total thickness of the diaphragm is 10µm-25µm; And / or, the porosity of the base membrane is 30% to 60%.

13. The battery according to claim 1, characterized in that, In the positive electrode active material layer, the mass ratio of nickel to manganese is 0.25-0.

43.

14. The battery according to claim 13, characterized in that, The particle size Dv50 of the positive electrode active material layer is 6µm-12µm.

15. The battery according to claim 13, characterized in that, The lithium nickel manganese oxide contains doping elements, which include one or more of zirconium, boron, tungsten, molybdenum, chromium, niobium, magnesium, tantalum, lanthanum, titanium, strontium, barium, cerium, tin, yttrium, aluminum, zinc, fluorine, phosphorus, and sulfur.

16. The battery according to claim 13, characterized in that, The lithium nickel manganese oxide has a coating layer on its surface, the coating layer comprising a coating material selected from one or more oxides of zirconium, boron, tungsten, molybdenum, chromium, niobium, magnesium, tantalum, lanthanum, titanium, strontium, barium, cerium, tin, yttrium, aluminum, zinc, fluorine, phosphorus, and sulfur.

17. The battery according to claim 13, characterized in that, The porosity of the positive electrode is 20%-40%.

18. The battery according to claim 13, characterized in that, The surface resistance of the positive electrode is 100mΩ-300mΩ.

19. The battery according to claim 1, characterized in that, The battery includes an electrolyte, and the electrolyte includes additives, which include any one or a combination of vinylene carbonate and fluoroethylene carbonate. The additive accounts for 0.1%-5% of the total mass of the electrolyte.

20. The battery according to claim 19, characterized in that, The electrolyte includes a solvent, which includes a carboxylic acid ester solvent, and the carboxylic acid ester solvent is selected from at least one of methyl formate, ethyl acetate, methyl acetate, and methyl propionate; The carboxylic acid ester solvent accounts for 5%-50% of the total mass of the electrolyte.

Citation Information

Patent Citations

  • Positive pole piece, preparation method and secondary battery

    CN119627105A

  • Lithium ion battery

    CN121790475A